A comparative analysis of occupational stress coping strategies in education specialists’ - Alifanovienė, Daiva; Gerulaitis, Darius; Kepalaitė, Albina; Šapelytė, Odeta; Vaitkevičienė, Asta (Special Education, 2017)
The article deals with the occupational stress strategies of education support specialists. Teachers are expected not only to work with students in the classroom but also to perform their duties as an administrator, to rally various resources for meeting the needs of the students and their parents as well as other community members; also to be an innovator, advisor and mediator etc., which creates a high level of (occupational) stress. The main objective of the article is to identify how education specialists’ develop stress coping strategies and to attempt to answer the following problem questions: What is the focus of Lithuanian education specialists’ in stress coping support strategies?  What are the links between the stress coping strategies used and socio-demographic characteristics? A quantitative research design was conducted to identify the stress coping strategies used by the specialists working in the education system.  (N= 478). Occupational stress experienced by education specialists becomes a serious test not only to the physical and mental health of the professional and his / her family, the potential loss of working capacity and also to the quality of work of the educational institution and the internal culture of the organisation.
Keywords: occupational stress; coping with the stress strategies; education support specialists